2019
DOI: 10.1007/s00402-019-03170-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term physical functioning and quality of life after pelvic ring injuries

Abstract: Background Pelvic ring injuries are serious injuries, often associated with substantial morbidity and mortality rates. The long-term consequences of these injuries might affect the patients’ personal life. Our aim was to assess the long-term effects of pelvic ring injuries on physical functioning and quality of life (QoL) using validated patient-reported outcome measures (PROMs) and comparing these results to normative data from the general population. Patients and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 20 publications
2
38
0
Order By: Relevance
“…Thirty-eight studies [ 8 , 9 , 25 , 26 , 28 – 30 , 32 – 36 , 10 , 37 44 , 46 , 47 , 11 , 48 54 , 56 , 18 – 22 , 24 ] used a pelvic-specific PROM, either as a single instrument or in combination with a generic PROM. Generic PROMs for physical functioning and quality of life were used in 15 studies [ 8 , 10 , 39 , 40 , 46 , 57 , 58 , 12 , 13 , 15 , 17 , 19 , 23 , 27 , 30 ]. The follow-up moment when these questionnaires were assessed ranged from six months to 15 years after the injury.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty-eight studies [ 8 , 9 , 25 , 26 , 28 – 30 , 32 – 36 , 10 , 37 44 , 46 , 47 , 11 , 48 54 , 56 , 18 – 22 , 24 ] used a pelvic-specific PROM, either as a single instrument or in combination with a generic PROM. Generic PROMs for physical functioning and quality of life were used in 15 studies [ 8 , 10 , 39 , 40 , 46 , 57 , 58 , 12 , 13 , 15 , 17 , 19 , 23 , 27 , 30 ]. The follow-up moment when these questionnaires were assessed ranged from six months to 15 years after the injury.…”
Section: Resultsmentioning
confidence: 99%
“…The mean score was 33 (SD 22). The Short Musculoskeletal Function Assessment (SMFA) was used in two studies [ 12 , 13 ]. One study [ 12 ] reported a score of 22 on the function index, 26 on the bother index and 21 on the lower extremity subscale.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anxiety and depression correlate moderately to strongly with the chronicity stage of this pain (Gerbershagen et al 2010). These patients tend to have a lower quality of life compared to the general population, including a longterm decrease in physical functioning, problems with activities of daily living and adverse psychological health (Banierink et al 2019). Increasing age, complex trauma and surgical management are all predictors of a poor quality of life amongst pelvic fracture patients (Holstein et al 2013).…”
Section: Postoperative Considerationsmentioning
confidence: 99%